A Rare Presentation of Mitral Stenosis - Saroj, Mandal; Manjunath, -; Shymalendu, Das; Debasrita, Mandal; Souvik, Kanjilal; Prakash, Hazra; Manotash, Panja (Journal of Medicine, 2016)
Abstract not available J MEDICINE January 2016; 17 (1) : 43-45